PENGARUH BIAYA KUALITAS TERHADAP PENJUALAN PADA CV. ANUGERAH MEBEL - Umi Kulsum, 03.05.52.0069; Nurhayati, Ida (Students Journal of Accounting and Banking, 2012)
This research represent research which testing quality coston sale. Company compete to do competition strategy in serving consumer like creating unique and different product and also with quality. A product can with quality if as according to consumer expectation and also price which is kompetitif. Intention of this research is to know influence of quality cost which consist of the prevention cost, appraisal cost, internal failure cost and eksternal failure cost to sale.The sample done using in this research is financial statement data,quality costand sale of period 2009-2011. The data sampeldone using counted 36 sampel.Data analysis done using is multipellinear regression. The result of research indicate that the quality cost which consist of the prevention cost, appraisal cost, internal failure cost expense and assessment have an effect on positive and signifikan to sale. While external failure cost have an effect on negativity to sale.Keyword: Quality Cost, Sale